Guided discovery-blended learning (GDBL) for critical thinking skill empowerment: A learning strategy in human excretory system - Suparini, S; Rusdi, R; Ristanto, Rizhal Hendi (Biosfer: Jurnal Pendidikan Biologi, 2020)
The research purpose is to learn Guided Discovery-Blended Learning (GDBL) strategy on students’ critical thinking skills in the human excretory system. The research method is quasi-experiment with pretest-posttest experiment and control group design. The research population includes all Grade XI MIPA in a senior high school in East Jakarta, Indonesia, of 144 students. As regards the sample, 71 students are selected that are divided into two classes, namely: XI MIPA-2 as a control class and XI MIPA-4 as an experimental class with GDBL. Data collection uses an integration test in an essay, student response to learning strategy and observation sheet of syntax implementation—the data analysis result using ANCOVA test proofs that the GDBL affects students’ critical thinking skill. The GDBL could foster thinking habits through independent rearrangement of a concept with guidance from the teacher using sourcebooks and online media. It is necessary to prepare biology teacher creativity to improve student’s critical thinking skills and to modify the GDBL so as it brings a better effect.